1996
DOI: 10.1007/bf02254962
|View full text |Cite
|
Sign up to set email alerts
|

Comparative FISH mapping of bovine cosmids to reindeer chromosomes demonstrates conservation of the X-chromosome

Abstract: Three X chromosome-specific bovine cosmids were used for fluorescence in situ hybridization mapping on reindeer (Rangifer tarandus) chromosomes, to test whether such large genomic clones could be used for comparative mapping across distantly related species. All three cosmids showed distinct unique hybridization sites on the reindeer X. Comparative map locations of these cosmids, together with the relative C-banding and genome size data on the X chromosomes of the two species, provide preliminary indications t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…For instance, Gallagher et al confirmed the conservation of X chromosome homology regions among members of Bovini, Boselaphini, Tragelaphini, domestic sheep and two deer species using BAC probes [ 27 ]. Comparative mapping of three X chromosome-specific bovine cosmids was employed in Rangifer tarandus gonosomes [ 33 ]. The results of another detailed study concerning conserved syntenies of the X chromosome in four Cervidae species are currently available [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gallagher et al confirmed the conservation of X chromosome homology regions among members of Bovini, Boselaphini, Tragelaphini, domestic sheep and two deer species using BAC probes [ 27 ]. Comparative mapping of three X chromosome-specific bovine cosmids was employed in Rangifer tarandus gonosomes [ 33 ]. The results of another detailed study concerning conserved syntenies of the X chromosome in four Cervidae species are currently available [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cosmid probes were labeled with biotin by nick-transla tion using the BioNick kit according to the supplier's (Life Technologies) instructions. FISH was carried out as described previously (Scherthan et al, 1994, Prakash et al. 1996.…”
Section: Probes Labeling and Fishmentioning
confidence: 99%
“…To our knowl edge, only five genes have been assigned by blot hybridization to Indian muntjac chromosomes 2, X, Yh and Y2 (Shows et al, 1976;Levy et al, 1992). Recently, Prakash et al (1996) showed that bovine cosmid probes can serve as infraorder FISH map ping tools among Pecora species. Three bovine X-chromosome specific cosmids were comparatively mapped to the Rangifer tarandus X chromosome (Prakash et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been due to a great variety of evolutionary interspecific rearrangements, which include obvious changes in centromere placement, heterochromatic variation, and autosomal translocation. Additionally, there is evidence of intrachromosomal rearrangement of the X with interpretations ranging from subtle band differences (Buckland and Evans, 1978a) to multiple, and probably quite complex, chromosomal changes (Hayes et al, 1991;Gallagher et al, 1994;Prakash et al, 1996Prakash et al, , 1997Robinson et al, 1997).…”
mentioning
confidence: 99%